Quantitative sensory testing in patients with sensitive skin. (2nd November 2018) - Huet, F.; Dion, A.; Batardière, A.; Nedelec, A.S.; Le Caër, F.; Bourgeois, P.; Brenaut, E.; Misery, L.
Summary: Sensitive skin is defined as unpleasant sensation, such as itch, pain or burning, in response to stimuli that would not normally cause these symptoms. It does not include patients with skin diseases such as eczema, which can cause these symptoms. Sensitive skin is claimed to affect 50% of women and 30% of men in Europe, and impairs their quality of life. It can be measured using a questionnaire, the Sensitive Scale. It is not clear whether these symptoms are due to changes in the skin's blood supply, a defect in the skin barrier or due to changes in the nerve supply to the epidermis (outermost layer of skin). The authors, based in Brittany, France, quantified heat‐pain threshold, a measure of touch sensitivity, in 21 individuals with Sensitive Skin Syndrome (having a Sensitive Scale score greater than 50) and 21 control subjects (Sensitive Scale score less than 20). The authors also quantified the degree of neuropathic (nerve‐related) pain in both groups using two questionnaires. They found a significantly reduced heat‐pain threshold and higher neuropathic pain scores in the individuals with sensitive skin, compared with controls. They conclude that these findings support the idea that sensitive skin is linked with abnormal function of the nerve endings in the skin. Conventionally, sensitive skin has been treated with moisturisers but the authors suggest that at least the more severely affected individuals may require a different approach to treatment. Abstract : Linked Article: Huet et al. Br J Dermatol 2018; 179 :1157–1162